Lossless, Passive Transportation of Low Surface Tension Liquids Induced by Patterned Omniphobic Liquidlike Polymer Brushes. (3rd October 2021) - Soltani, Mohammad; Golovin, Kevin
Abstract: Surfaces enabling directional liquid transportation are of great interest for a wide range of applications such as water collection, microfluidics, and heat transfer systems. Surfaces capable of lossless, long‐range passive transportation of low surface tension (LST) liquids using wettability patterned, liquidlike coatings with minimal contact angle hysteresis are reported. Lossless LST droplet travel distances over 150 mm are achieved, enabled by a two‐phase transportation mechanism: morphological transformation from a bulge to a channel shape, followed by directional transportation along the asymmetrical wedge‐shaped channel. The developed surfaces can split, merge, and precisely transport various low‐surface tension liquids, including alcohols, alkanes, and solvents. The developed transportation strategy can also enhance LST liquid dropwise condensation through continuous removal of the condensate, even on horizontally positioned surfaces without the assistance of gravity. Abstract : Liquidlike omniphobic polymer brushes are used to pattern smooth surfaces with channels that transport both polar and nonpolar low surface tension liquids at large distances, passively and without fluid loss. Such channels perform many complex fluidic tasks, such as droplet splitting, mixing, moving along nonlinear pathways, and even stable dropwise condensate collection of low surface tension liquids on horizontal surfaces.